Pemanfaatan Pohon Keputusan dan Graf Dalam Pemetaan Karyawan Berbasis Kompetensi - Abdul Rahman Kadafi; Eko Setia Budi; Raden Bagus Dimas Putra (JURIKOM (Jurnal Riset Komputer), 2019)
The organization is constantly undergoing changes to keep developing following the times. Analysis of opportunities and threats that exist, will affect the internal performance of the organization, both in the form of strengths and weaknesses in the organization. Decision tree is a prediction model using tree structure or hierarchical structure. Competence is not just a skill but a skill that can be manifested, competency is not just a motive, but must have a certain behavior that reflects a motive. Mapping employee competencies and potential begins with an assessment of employee competencies and potential, or competency assessment. It is important to assess competency to ensure that the right person gets the right job at the right time. The competency-based employee mapping flow is an implementation of directed graphs, with the ultimate goal being employee mapping. Decision tree theory and graphs can be used in creating competency-based employee mapping flows